PENGARUH PERUBAHAN TARIF PAJAK PENGHASILAN BADAN MENURUT PP NO.30 TAHUN 2020 , INSENTIF PAJAK DAN NON PAJAK TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI MAKANAN DAN MINUMAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFT - Fitriadi, Fitriadi (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2022)
This study aims to analyze the Food and Beverage companies listed on the Indonesia Stock Exchange in managing earnings, with changes in corporate income tax rates based on tax incentives or non-tax incentives. The sample of this research is 19 companies listed on the Indonesia Stock Exchange, which have published their financial statements from 2019-2020. The analysis method in this study uses a different t-test using one sample t-test and multiple linear regression analysis. The results show that: 1) the company performs earnings management before and after the reduction in corporate income tax rates; 2) food and beverage companies perform earnings management which is influenced by tax incentives (tax planning and net deferred tax liability) and non-tax incentives (company size, corporate debt level, earnings pressure).